Soil biota response to experimental rainfall reduction depends on the dominant tree species in mature northern Mediterranean forests. (March 2021) - Aupic-Samain, Adriane; Santonja, Mathieu; Chomel, Mathilde; Pereira, Susana; Quer, Elodie; Lecareux, Caroline; Limousin, Jean-Marc; Ourcival, Jean-Marc; Simioni, Guillaume; Gauquelin, Thierry; Fernandez, Catherine; Baldy, Virginie
Abstract: Soil organisms play a major role on litter decomposition process and nutrient cycling in forest ecosystems. These organisms are extremely sensitive to environmental conditions such as soil temperature and moisture conditions which control their demographic parameters and activity. The ongoing climate change can therefore directly affect soil biota communities and the processes they drive. Besides, climate change can also indirectly affect soil biota by altering tree functional traits (e.g., N, Ca, Mg, water holding capacity) with cascading effects on the litter quality. The aim of this study was to determine the relative effects of increased drought and litter type on microbial biomass (bacteria and fungi) and mesofauna abundance (Collembola and Acari) in three experimental sites representative of the three main forests encountered in the northern part of the Mediterranean Basin (dominated by either Quercus pubescens, Quercus ilex or Pinus halepensis ) where rainfall exclusion experiments were taking place. At each site, and in each precipitation treatment (natural and amplified drought plots), we collected and transplanted foliage litters (i.e., species × drought level). After two years, we reported a litter species effect: Q. pubescens litter presented consistently the higher abundance of all soil biota groups compared to Q. ilex and P. halepensis litters in each forest. Surprisingly, despite that the amplified drought treatment induced a modification of the litter quality, we did not reported an indirect reduced precipitation effect on soil biota parameters. While Oribatid Acari abundance decreased with amplified drought in all three forest types, the direct effects on the other soil biota groups were forest-dependent. In P. halepensis forest, amplified drought resulted in higher bacterial and fungal biomasses but lower Collembola abundance. In Q. ilex forest both Collembola and predatory Acari abundances decreased with amplified drought. In addition, the positive relationships between Collembola and Oribatida abundances and litter mass loss disappeared under amplified drought conditions in both Q. ilex and P. halepensis forests. These results suggest a key role played by Ca, Mg, specific leaf area (SLA) and water holding capacity (WHC) as drivers of soil biota parameters. Finally, the study highlights that within the same Mediterranean region, climate change could differently alter the soil organisms inhabiting the litter layer and their contributions to the decomposition process depending on the tree species and soil biota group considered. Highlights: Chemical (Ca, Mg) and physical (WHC, SLA) litter characteristics drive soil biota. Drier conditions lead to higher microbial biomass but lower mesofauna abundance. Drier conditions alter plant litter quality without cascading effect on soil biota. Drier conditions suppress soil fauna-litter decomposition efficiency relationships.